Co-occurrence of Methanosarcina mazei and Geobacteraceae in an iron(III)-reducing enrichment culture - Shiling eZheng; Hongxia eZhang; Hongxia eZhang; Ying eLi; Ying eLi; Hua eZhang; Oumei eWang; Jun eZhang; Fanghua eLiu (Frontiers in Microbiology, 2015)
Methanosaeta harundinacea and Methanosarcina barkeri, known as classic acetoclastic methanogens, are capable of directly accepting electrons from Geobacter metallireducens for the reduction of carbon dioxide to methane, having been revealed as direct interspecies electron transfer (DIET) in the laboratory co-cultures. However, whether their co-occurrences are ubiquitous in the iron (III)-reducing environments and the other species of acetoclastic methanogens such as Methanosarcina mazei are capable of DIET are still unknown. Instead of initiating the co-cultures with pure cultures, two-step cultivation was employed to selectively enrich iron (III)-reducing microorganisms in a coastal gold mining river, Jiehe River, with rich iron content in the sediments. First, iron (III) reducers including Geobacteraceae were successfully enriched by 3-months successive culture on amorphous Fe(III) oxides as electron acceptor and acetate as electron donor. High-throughput Illumina sequencing, terminal restriction fragment length polymorphism (T-RFLP) and clone library analysis based on 16S rRNA genes revealed that the enrichment cultures actively contained the bacteria belong to Geobacteraceae and Bacilli, exclusively dominated by the archaea belong to Methanosarcinaceae. Second, the enrichment cultures including methanogens and Geobacteraceae were transferred with ethanol as alternative electron donor. Remarkably, aggregates were successively formed in the enrichments after three transfers. The results revealed by RNA-based analysis demonstrate that the co-occurrence of Methanosarcina mazei and Geobacteraceae in an iron (III)-reducing enrichment culture. Furthermore, the aggregates, as close physical contact, formed in the enrichment culture, indicate that DIET could be a possible option for interspecies electron transfer in the aggregates.